You are on page 1of 6

EQUATIONS When simplifying algebraic expressions, we perform operations within parentheses first and then exponents and then

multiplication and then division and then addition and lastly subtraction. This can be remembered by the mnemonic PEMDAS Please Excuse My Dear Aunt Sally When solving equations, however, we apply the mnemonic in reverse order: SADMEP. This is often expressed as follows: inverse operations in inverse order. The goal in solving an equation is to isolate the variable on one side of the equal sign (usually the left side). This is done by identifying the main operation addition, multiplication, etc. and then performing the opposite operation. An equation means that the terms on either side of the equal sign are equal in every way. Hence, any property one side of an equation has the other side will have as well. Following are some immediate deductions that can be made from simple equations. Equation y-x=1 Deduction y>x . That is, x and y can differ only in Sign y=x

y>0 Both x and y are positive or both x and y are negative y=x=0 3y=4x and x>0 and x<0 and y is positive y < x and y is negative

y=2x y=2x+1

y is even y is odd

3) Solve the resulting equation: 5x 5x 9x 2(10 2x) = 7 20 + 4x = 7 20 = 7 . you still need to know a standard method for solving these types of systems. y = z. For example. you solve an equation for. you can solve a system of two equations in two unknowns by merely adding or subtracting the equations instead of solving for one of the variables and then substituting it into the other equation METHOD OF SUBSTITUTION (Four-Step Method) Although on the SAT you can usually solve a system of two equations in two unknowns by merely adding or subtracting the equations. y by isolating y on one side of the equality symbol. say. or both  In Algebra. you are often asked to solve for an entire term. 3 y by isolating it on one side. a system of 3 equations will be written as one long ‘triple’ equation.  Sometimes on the SAT. can be written more compactly as x =y = z. however.yx=0 y=0 or x=0. x = z. the three equations x = y. say. The four-step method will be illustrated with the following system: 2x + y = 10 5x 2y = 7 1) Solve one of the equations for one of the variables: Solving the top equation for y yields y = 10 2x.  Often on the SAT. 2) Substitute the result from Step 1 into the other equation: Substituting y = 10 2x into the bottom equation yields 5x 2(10 2x) = 7. On the SAT.

y=2 C) x=2. then a . i..y=2 B) x=1.b = (A) -4 (B) -1 (C) (D) (E) 2 Solution: Translating the sentence into an equation gives a + 3a = b + 3b .9x = 27 x=3 4) Substitute the result from Step 3 into the equation derived in Step 1: Substituting x = 3 into y = 10 Example: Consider x A) x=2. so we obtain x = 2. 4) Subtracting these equations yields an equation in y.y=1 D) x=1.4 (1) (2) Find x and y? 2x yields y = 10 2(3) = 10 6 = 4.y=1 Solution: x + 2y = 4 x+y=3 x + 2y − (x + y) = 4 – 3 y=1 Reinserting this result into (2) gives x + 1 = 3. the solution of the system of equations is the ordered pair (3. Hence.e. (1)-(2) gives . Check the results by substituting them into (1)! Example: If a + 3a is 4 less than b + 3b.

b = -1 Hence. SADMEP).5) A) x = 6 B) x = -6 C) x = 5 D) x=-5 .Combining like terms gives 4a = 4b . the answer is (B). Example: Solve the following equation for x: 2x + y = 5 A) B) C) D) Solution: The main operation is addition (remember addition now comes before multiplication.4b = -4 Finally. dividing by 4 gives a . Undoing the multiplication Canceling the 2 on the left side yields Practice Questions 1) Solve the following equation for x: 3x .y = 5 .y Simplifying yields by dividing both sides by 2 yields 2x = 5 . so subtracting y from both sides yields 2x + y .4 = 2(x .4 Subtracting 4b from both sides gives 4a .y The only operation remaining on the left side is multiplication.

2) x .5) 5) Use the substitution method to solve the system.2) Solve simultaneous equation by substitution method 2x .9y = 0 …(i) … (ii) A) (9.5) C) (-2.5) 4) Solve the following system by substitution.3) D) (1. 2x – 3y = –2 4x + y = 24 A) (-4.2) B) (7.5) . 7x + 4y = 6 2x – y = -9 A) (2.5) B) (-2.2) C) (-9.4) D) (3.3) B) (5.4) B) (2.-2) D) (-7.-5) D) (3.2) C) (5.18y = 27 3) Solve simultaneous equation by substitution method 43x + 31y = 241 …(i) 31x + 43y = 277 …(ii) A) (-2.5) C) (-2.